A Novel Plug-Based Vascular Closure Device for Percutaneous Femoral Artery Closure in Patients Undergoing Minimally-Invasive Valve Surgery - Schaefer, Andreas; Sarwari, Harun; Reichenspurner, Hermann; Conradi, Lenard (Frontiers in Cardiovascular Medicine, 2021)
Objectives: Surgical exposure of groin vessels to establish cardiopulmonary bypass (CPB) for minimally-invasive valve surgery (MIS) is standard of care but may result in postoperative wound healing disorders or seroma formation. Therefore, adaption of transcatheter techniques for fully percutaneous insertion of CPB cannulae may improve clinical results. We herein analyze a single center experience with a novel plug-based vascular closure device for MIS. Methods: Between 03/2020 and 02/2021 MIS using the MANTA™ (Teleflex Medical Inc., Wayne, PA, USA) vascular closure device was performed in 28 consecutive patients (58.8 ± 10.6 years, 60.3% male, logEuroSCORE II 1.1 ± 0.8%) receiving mitral and/or tricuspid valve repair/replacement. Concomitant procedures were left atrial appendage occlusion and cryoablation for atrial fibrillation in 21.4% (6/28) and 10.7% (3/28) of patients, respectively. Data were retrospectively analyzed in accordance with standardized M-VARC definitions. MANTA™ device success and early safety was defined as absence of any access site or access related vascular injury and major and life-threatening bleeding complications. Results: MANTA™ device success with immediate hemostasis and early safety were 96.4% (27/28). In one case, device failure necessitated surgical cut down without further complications. Mean aortic cross clamp time and cardiopulmonary bypass were 96.5 ± 24.2 min and 150.2 ± 33.6 min. Stroke, renal failure or myocardial infarction were not observed. Intensive care unit and total hospital stay were 1.7 ± 0.8 days and 10.1 ± 5.7 days. Overall 30-day mortality was 0%. Post-procedure echocardiography presented one case of residual moderate tricuspid regurgitation and competent valves in all other cases. Conclusions: The MANTA™ device is safe and effective in MIS. Its ease of use and effectiveness to achieve immediate hemostasis have further simplified MIS.